Effect of febuxostat on clinical outcomes in patients with hyperuricemia and cardiovascular disease. (15th February 2022) - Konishi, Masaaki; Kojima, Sunao; Uchiyama, Kazuaki; Yokota, Naoto; Tokutake, Eiichi; Wakasa, Yutaka; Hiramitsu, Shinya; Waki, Masako; Jinnouchi, Hideaki; Kakuda, Hirokazu; Hayashi, Takahiro; Kawai, Naoki; et al.
Abstract: Background: We previously reported on the FREED study, which found that febuxostat reduced the risk of adverse clinical outcome in patients with asymptomatic hyperuricemia without gout. We have now investigated outcomes in subgroups of FREED patients with and without a history of cardiovascular disease (CVD). Methods: We performed a post hoc subgroup analysis of 1070 patients randomized to the febuxostat or non-febuxostat group and followed for 36 months. Results: At baseline, 234 patients (21.9%) had a history of CVD, including 86 patients with stroke (36.8%), 90 with coronary artery disease (38.5%), 74 with heart failure (31.6%), and 25 with vascular disease (10.7%). The risk for the primary composite endpoint, i.e., cerebral, cardiovascular, and renal events and all deaths, was higher in patients with CVD than in those without CVD (34.2% vs 23.7%; p  < 0.001). Treatment with febuxostat lowered rates of the primary composite endpoint in patients with CVD (hazard ratio [HR] 0.601, 95% CI 0.384 to 0.940, p  = 0.026), and these effects were consistently observed in subgroups with and without CVD ( p  = 0.227 for treatment by subgroup interaction). Furthermore, in the subgroup with CVD, all-cause mortality was significantly lower in the febuxostat group than in the non-febuxostat group (HR 0.160, 95% CI 0.047 to 0.547, p  = 0.004), with a significant subgroup interaction ( p  = 0.007 for treatment by subgroup interaction). Conclusions: In patients with asymptomatic hyperuricemia without gout, febuxostat reduces the risk of the composite of cerebral, cardiovascular, and renal events and death in the secondary prevention setting. Highlights: 1070 patients with hyperuricemia were randomized to febuxostat or non-febuxostat treatment. Patients with hyperuricaemia and CVD had an increased risk for cardiovascular events. Fewer CV events and all-cause death were observed in febuxostat group than non-febuxostat group.